Is Profitability the Missing Link? Green Financing, Capital Adequacy, Credit Risk, and Efficiency in Driving Firm Value - Tri Kartini Putri; Asep Risman (Greenation Research & Yayasan Global Resarch National, 2026)
This study provides empirical evidence on whether profitability remains a key link in the influence of emerging factors, such as green financing, and traditional factors on firm value. The study uses panel data from six conventional commercial banks included in the LQ45 index during the 2019–2023 observation period. The results indicate that neither Green Financing nor capital adequacy directly impacts profitability or firm value. However, credit risk and efficiency exhibit significant negative effects on both outcome variables, while profitability itself significantly positively impacts firm value. Other findings indicate that profitability is only a key link in the influence of operational efficiency on firm value but does not serve as a significant pathway for Green Financing, capital adequacy, and credit risk. Overall, this study underscores that operational discipline (cost efficiency) has a greater impact on market value than sustainable financing initiatives and capital adequacy.